Process optimization of biodiesel production from wild rapeseed (Brassica campestris) - Ramírez, Héctor (2012)
The objectives of this study were, to optimize the performance of biodiesel from rapeseed wild oil depending on the molar ratio methanol / oil, the concentration of NaOH and KOH homogeneous catalysts, temperature and time of transesterification through the response surface methodology, and determining the physicochemical characteristics of biodiesel obtained under optimized conditions. A Plackett and Burman (PB12) design was applied for the screening stage and a rotatable central composite design (DCCR) for the final optimization. The conditions that maximize the yield of biodiesel (77.8%) were obtained at concentrations of 0 to 0.2% NaOH and 0.4 to 0.6% KOH, with time from 77 to 81 minutes, keeping constant the molar ratio of methanol/oil in 6/1 and a temperature of 60 °C. The physicochemical properties of biodiesel obtained under optimized conditions meet the technical specifications given by ASTM D6751 - 07 and EN14214.